Cyclophosphamide and tucotuzumab (huKS-IL2) following first-line chemotherapy in responding patients with extensive-disease small-cell lung cancer. Issue 10 (November 2015) - Gladkov, Oleg; Ramlau, Rodryg; Serwatowski, Piotr; Milanowski, Janusz; Tomeczko, Janusz; Komarnitsky, Philip B.; Kramer, Daniel; Krzakowski, Maciej J.
<x xml:space="preserve">Abstract</x> The humanized KS-interleukin-2, tucotuzumab (huKS-IL2; EMD 273066), is an EpCAM-specific immunocytokine with reported immunologic activity in combination with cyclophosphamide. This Phase 2, randomized, open-label study compared tucotuzumab/cyclophosphamide, administered as maintenance, with best supportive care (BSC) in patients with extensive-disease small-cell lung cancer (ED-SCLC) who responded to first-line platinum-based chemotherapy with/without prophylactic cranial irradiation (PCI). Patients received cyclophosphamide (300 mg/m2, Day 1 of every 3-week cycle), followed by tucotuzumab (1.5 mg/m2, Days 2–4) until disease progression. The primary endpoint was 6-month progression-free survival (PFS); the secondary objectives included overall survival (OS), treatment response, and safety. The 6-month PFS rate was lower in the tucotuzumab/cyclophosphamide group (n=64) than in the BSC group (n=44): 6.4 versus 12.2% [hazard ratio (HR): 0.98; 80% confidence interval (CI): 0.74–1.31]. HRs for PFS, time to progression, and OS indicated a similar risk of disease progression and death in both groups and best overall responses were generally comparable. For patients with previous PCI (n=26), there was a nonsignificant trend toward prolonged median PFS (1.7 vs. 1.5 months; HR: 0.60; 80% CI: 0.33–1.11) and OS (21.5 vs. 14.3 months; HR: 0.58; 80% CI: 0.31–1.05) in the tucotuzumab/cyclophosphamide group. Adverse events were more frequent with tucotuzumab/cyclophosphamide (92.2%) than with BSC (47.7%). Tucotuzumab/cyclophosphamide was well tolerated in ED-SCLC patients, but did not show PFS or OS benefits compared with BSC. The observed trend toward prolonged PFS and OS in the subgroup of patients receiving previous PCI may support further confirmation in a larger population.